2014
DOI: 10.7314/apjcp.2014.15.19.8245
|View full text |Cite
|
Sign up to set email alerts
|

5,10-Methylenetetrahydrofolate Reductase Polymorphisms and Colon Cancer Risk: a Meta-analysis

Abstract: Previous studies investigating the association between 5,10-methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms and colon cancer risk have generated conflicting results. The aim of our meta-analysis was to clarify the precise association. A systematic literature search was conducted to identify all relevant studies. Pooled odds ratio (ORs) with 95% confidence interval (CI) were used to estimate the strength of the association. In this meta-analysis, a total of 13 articles, involving 5,386 cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Polymorphisms in the MTHFR gene could alter the enzyme activity and influence the capacity of the MTHFR enzyme, thereby altering the folate metabolism, and DNA synthesis and repair. Previous studies have reported an association between the polymorphisms in the MTHFR gene and increased risk of several types of cancers, such as head and neck cancer, childhood leukemia, lung cancer, colon cancer, and skin cancer (Deng et al, 2014;Fang et al, 2014;Niu et al, 2015;Pei et al, 2015;. However, the results of these studies have been inconsistent, with the differences generally being attributed to the different types of cancers, sample size, and study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the MTHFR gene could alter the enzyme activity and influence the capacity of the MTHFR enzyme, thereby altering the folate metabolism, and DNA synthesis and repair. Previous studies have reported an association between the polymorphisms in the MTHFR gene and increased risk of several types of cancers, such as head and neck cancer, childhood leukemia, lung cancer, colon cancer, and skin cancer (Deng et al, 2014;Fang et al, 2014;Niu et al, 2015;Pei et al, 2015;. However, the results of these studies have been inconsistent, with the differences generally being attributed to the different types of cancers, sample size, and study populations.…”
Section: Discussionmentioning
confidence: 99%
“…If the heterogeneity test result returned P > 0.1, the pooled ORs were analyzed using the random-effects model ( DerSimonian and Laird, 1986 ), or else, the fixed effects model was used ( Mantel and Haenszel, 1959 ). Sensitivity analyses were also performed after sequential removal of each study ( Fang et al, 2014 ). We also tried to assess the source of heterogeneity by region, publication year, control source, and sample size ( He et al, 2014; Xue et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, the 5-methyltetrahydrofolate is the main circulatory form of folate in the body and provides a methyl group to convert the amino acid homocysteine into methionine, which is the precursor of S-adenosylmethionine (SAM). SAM is the major methyl donor in the cell and takes part in DNA methylation [ 8 ]. Therefore, MTHFR not only plays a role in making proteins and other important compounds, but also is an important factor in DNA methylation, synthesis, and repair [ 9 ].…”
Section: Introductionmentioning
confidence: 99%